Reefing Viability Index for Rigs-to-Reefs (R2R) in Malaysia. (11th November 2020) - Mohd, Mohd Hairil; Rahman, Mohd Asamudin A.; Nazri, Muhammad Nadzrin; Tan, Chun Hong; Mohamad, Yuzwan; Lim, Chuin Siew; Mustapa, Baharim; Shaari, Hasrizal; Hii, Yii Siang; Kim, Do Kyun
Abstract : Decommissioning of the offshore platform as an artificial reef, known as Rigs-to-Reefs (R2R), has become a sustainable approach for oil companies. The platform was reused to serve the underwater ecosystem as an artificial reef for a new marine ecosystem which helps to tackle food security issue. This paper presents the findings of the formulation of the reefing viability index to recognize an offshore region that can be used for R2R projects within the South China Sea. The combined effects of spatial data, numerical modelling, and geographic system (GIS) are proposed to study the relationship of spawning ground coral reefs, diversity, and planula larvae in the process of colonization to establish a map of the reef potential environment. Coral connectivity and spawning behaviour were studied to determine the possible source of coral seedling released during the spawning season, twice a year. A geographic reef viability index was established consisting of seven parameters which are coral larval density, pelagic larval length, sea currents, temperature, chlorophyll-a, depth, and substrate availability. The ocean hydrodynamic model was designed to resemble the pattern of larval scattering. By using the simulations and rankings, there were 95 (21%) sites which could probably be used for in situ reefing, whereas 358 (79%) sites were likely ideal for ex situ reefing. Validation of the viability index was carried out using media footage assessment of remotely operated vehicle (ROV).